A is for Africa - Onyefulu, Ifeoma (Frances Lincoln Ltd, 1995)
Stunning color photographs depict everyday life in Nigeria in this unusual ABC book by a talented African photographer.
Keywords: Alphabet; Concepts; Juvenile Nonfiction